Promoting "KKN di Desa Ponari" to Millennials: A Film Marketing Public Relations Approach - Khairun Alfi Syahri (I-Pop: International Journal of Indonesian Popular Culture and Communication, 2022)
The popularity of KKN di desa Penari film is inseparable from a directed and integrated marketing communication strategy. This article describes the marketing public relations strategy carried out by MD Entertainment as a producer in promoting the KKN di Desa Penari film. MD Entertainment uses various communication channels and public outreach by leveraging the power of digital storytelling through social media. Myths and rumors are propagated through digital conversations, thereby raising public awareness and curiosity. This study can be an insightful reference for the film industry and future researchers who want to understand more about the strategy behind this one of the highest-grossing films in Indonesia.